ANALISIS KEMAMPUAN MENYELESAIKAN SOAL FISIKA BERKATEGORI LOTS DAN HOTS SISWA KELAS X MAN 1 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Learning success determines the extent to which students' ability to achieve learning outcomes. Analysis of students 'abilities in solving problem can be used by the teacher as a tool in determining the extent of students' abilities, so that better learning methods can be carried out. The purpose of this study was to determine the ability of students in solving LOTS and HOTS problems in physics. The population in this study were 108 students of class X MAN 1 Pekanbaru. Samples were taken randomly and obtained a sample of 30 students. The research instrument is in the form of objective questions with four answer choices which are arranged based on Anderson's revised Bloom taxonomy. The data were collected by giving objective test questions to the research sample. Data analysis in this study used descriptive analysis with percentage techniques, which provides an overview of the level of student ability. The results of the study provided information that the average student achievement in answering LOTS questions was in the good category with a percentage of 67.3%. The respective percentage indicators are C1 52%, C2 57.3%, C3 92.7%. The average student achievement in answering HOTS questions was in the good category with a percentage of 68.9%. The respective percentage indicators are C4 58.7%, C5 71.3%, C6 77.3%.Key Word: Low Order Thinking Skills, High Order Thinking Skills, Physics Problem, Physics Education